The air raid book club : a novel [large type] - Lyons, Annie (Harper Large Print, an imprint of HarperCollins Publishers, 2023)
"London, 1938: The bookstore just doesn't feel the same to Gertie Bingham ever since the death of her beloved husband Harry. Bingham Books was a dream they shared together, and without Harry, Gertie wonders if it's time to take her faithful old lab, Hemingway, and retire to the seaside. But fate has other plans for Gertie. In Germany, Hitler is on the rise, and Jewish families are making the heart-wrenching decision to send their children away from the growing turmoil. After a nudge from her dear friend Charles, Gertie decides to take in one of these refugees, a headstrong teenage girl named Hedy. Willful and fearless, Hedy reminds Gertie of herself at the same age, and shows her that she can't give up just yet. With the terrible threat of war on the horizon, the world needs people like Gertie Bingham and her bookshop. When the Blitz begins and bombs whistle overhead, Gertie and Hedy come up with the idea to start an air raid book club. Together with neighbors and bookstore customers, they hold lively discussions of everything from Winnie the Pooh to Wuthering Heights. After all, a good book can do wonders to bolster people's spirits, even in the most trying times. But even the best book can only provide a temporary escape, and as the tragic reality of the war hits home, the book club faces unimaginable losses. They will need all the strength of their stories and the bonds they've formed to see them through to brighter days"--